Mr. Lever's address on visit of International Housing Conference to Port Sunlight, 9 August 1907 - Leverhulme, William Hesketh Lever, Viscount, 1851-1925 (1909)
1909 1909 1900s 10 pages APPENDIX. xix. The following table gives the percentage of married men amongst these various grades : — Lower Grade Workmen..................78% Higher Grade Workmen..................96% Lower Grade Clerks ... ............71% Higher Grade Clerks ..................66% Lower Grade Business Men ... ... 96% Higher Grade Business Men ... ... 92% The higher proportion of married men among the higher grade of workingmen is very striking, every man over the age of 40 being married and having a wife living. Mr. Fraser next compares the different grades with reference to the number of children, the children who were living and under the age of 17 at the end of 1905 were classified according to the ages and grades of their fathers and the average number of children per married man in each grade was found to be as follows: — CHILDREN UNDER 17 PER MARRIED MAN. Ages of Fathers Workman Workman Clerk Clerk Business Man Business Man Lower Grade. Higher Grade. Lower Grade. Higher Grade. Lower G. Higher G. 25—29 ..1.0. ..1.7. .. .4 ..1.0 - — 30—34 ...2.0 ..2.7. .. 1.0 ..2.0 ...1.0. . 1.7 35—39 ..2.9 ..3.5 .1.7 ...1.5 ..1.7.. . 2.5 40—44 ...2.6 ..4.1. .. — .. — ...1.2. . 2.5 45—49 ..3.1. ..2.9. .. 2.0 ..2.0 ...2.2. . 1.6 50—54 ..2.9 ..2.9. .. — ..6.0 ...1.0. . 2.2 55—59 ... .4 ..1.0. .. — ..1.0 .. — . . — 60—69 ... — .. — . .. — ... — .. — .. . — From this Table it will be seen that the higher grade of workingman take the lead in a most remarkable manner. Mr. Fraser next calculated, taking the number of children per higher grade workman as the standard, the percentage there actually was in the other grades, and the result was shown to be as follows: — PERCENTAGE OF CHILDREN UNDER 17 PER MARRIED MAN COMPARED WITH THE STANDARD OF CHILDREN OF HIGHER GRADE WORKING MEN. Working Men (Higher grade)............100 % (Lower grade)......................... 77.9 % Clerks (Higher grade).....................61.1% „ (Lower grade)....................................... 42.6% Business Men (Higher grade)............ 62.4% „ (Lower grade).................. 47.5% Mr. Fraser next considers the question of children from another point of view. The above table deals with the number of children per married man. Next Mr. Fraser calculates the number of children per male employee in each of the above grades, whether the employee be married or single. This table, it will be noted, introduces as a further factor in the calculation the percentage of men unmarried at each grade. The result obtained in calculating the number of children under 17 per man to each grade, taking the higher grade working man as the standard, was as follows: — Working Men (Higher grade)............100 % „ (Lower grade)................. 65.2% Business Men (Higher grade)............ 58.3% „ (Lower grade)................. 46.8 % Clerks (Higher grade........... 45.5% „ (Lower grade)...................................... 33.0% Practically it will be seen that the male employees of all the other grades taken together rise only half way to the standard set by the higher grade working men. Mr. Fraser next prepared statistics in which the children are grouped in families and the average number of children under 17 per family arrived at was as follows: — Working Men (Higher grade)..................3.1 „ (Lower grade).............................2.1 Business Men (Higher grade)..................1.8 „ (Lower grade)...............................1.4 Clerks (Higher grade)..........................2.0 „ (Lower grade).............................................1.2 The preponderance of large families amongst the higher grade workingmen is very striking, and it was also found that more than half the children of the higher grade of workingmen were in families of more than four children. So far as Port Sunlight is concerned it is clear that this is the grade which provides the increase of population. If Port Sunlight is representative of the general population of the United Kingdom then we can assume that the increase of population, and in fact the great majority of the future population will be provided by the higher grade of working-men, the most intelligent and the fittest of their class, and we may take the most optimistic view of the future. But if Port Sunlight is not representative of the general population of the United Kingdom, the figures are not the less interesting. They show that under favourable conditions, as regards employment and housing and general environment, such as exist at Port Sunlight, the most intelligent of the working classes will provide their full share and even more of the future population, and that Port Sunlight shows the way to the rest of England. Another fact disclosed by Mr. Fraser's statistics is that it will be seen the marriage-rate varies in accordance with what may be called the surplus income of the man. By the word "surplus" income I wish to draw our thoughts away from actual income. A manager in receipt of a few hundreds a year, living in a certain style, may have little or no surplus income. A clerk on £2 a week dressing in cloth has less surplus income than a mechanic on 35/- per week. Bearing this fact in mind the figures clearly show that the marriage-rate is higher among the better class artizans, which is the class that enjoys of all workers, the largest amount of surplus income. A clerk stands at the lowest as far as surplus income is concerned. This you will see affects both the marriage-rate and birth-rate. I must apologize for occupying so much of your time with these statistics but they are essentially necessary in considering Garden City life and its effect upon the development of the race. I am positive from all the statistics available, that the most healthy conditions of the human race are obtained where the home unit exists in a self-contained house with the living rooms on the ground floor, and the bedrooms on the floor immediately over. All tenement dwellings, flats, and such devices for crowding a maximum amount of humanity in a minimum amount of ground space are destructive of healthy life, and whilst they may be endured possibly by adults are seriously and permanently injurious to the growth and development of children. The building of 10 to 12 houses to the acre is the maximum that ought to be allowed, any excess beyond this ought to be strictly prohibited by building bye-laws, whilst the width of roadway ought to be increased to a minimum of 45 feet, the necessity for paving and macadamizing of the whole roadway and flagging the whole of the footpath, kerbing and channelling of the gutters should be dispensed with in 36/H24/20